2020
DOI: 10.1021/acsanm.0c00659
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Mesoporous Nickel Oxide as a Highly Sensitive Nonenzymatic Glucose Sensor

Abstract: In this paper, we present a novel laser-induced oxidation procedure for in situ formation of nickel oxide nanoporous structures directly onto the nickel surface as a highly sensitive nonenzymatic glucose sensor. The formation of mesoporous nickel oxide is confirmed by field-emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray diffraction. Electrochemical properties of the pristine and laser-induced oxidized nickel (LIO-Ni) films were studied using cyclic voltammetry and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 85 publications
0
33
1
Order By: Relevance
“…These results indicated that the redox reaction on the CNT-NH 2 -Ag/PS paper electrode was a diffusion-controlled electrochemical process. [62][63][64] whereas their mechanisms for glucose redox in neutral [66][67][68] and acidic solutions were not clear. [69][70][71] For the current CNT-NH 2 -Ag/PS paper electrode, the redox reaction of glucose was performed in a neutral solution (Na 2 SO 4 system).…”
Section: Fabrication and Characterization Of The Cnt-nh 2 -Ag/ps Pape...mentioning
confidence: 99%
“…These results indicated that the redox reaction on the CNT-NH 2 -Ag/PS paper electrode was a diffusion-controlled electrochemical process. [62][63][64] whereas their mechanisms for glucose redox in neutral [66][67][68] and acidic solutions were not clear. [69][70][71] For the current CNT-NH 2 -Ag/PS paper electrode, the redox reaction of glucose was performed in a neutral solution (Na 2 SO 4 system).…”
Section: Fabrication and Characterization Of The Cnt-nh 2 -Ag/ps Pape...mentioning
confidence: 99%
“…NiO is a well‐known antiferromagnetic (AFM) material with high Néel temperature (523 K) and has large applications in the fields of memory devices, rechargeable batteries, gas sensors, and fuel cells. [ 1–7 ] Moreover, electrically insulating NiO thin films are widely used in spintronic devices for the enhancement of spin currents. [ 8,9 ] The AFM and spin behavior of NiO nanostructures depends on the parameters like particle size, morphology, structure, Ni vacancy concentration, and surface defects.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21,22 ] Laser‐assisted dewetting at molten phase has been described in the literature. [ 23 ] The laser‐assisted process shows several advantages with respect to conventional physical and chemical processes, such as green, tunable fabrication in ambient condition and scalability. [ 24–27 ]…”
Section: Introductionmentioning
confidence: 99%